Managing green redefining the Local Government Units' environmental role - Sajo, Tomas A.; Pacete, Ofelia T. (Danyag :the UPV journal of humanities and social sciences)
"There are no easy and tailored solutions to the urgent environmental and challenges in the 21st century. For local government units (LGU's), particularly the barangay, mechanisms have to be installed to mobilize forces and resources to create a breakthrough in redefining their environmental roles from mere garbage collectors to proactively green managers. The major findings indicate LGUs' highly significant understanding of their changing environmental roles and responsibilities , and acceptance of their present social and environmental roles and responsibilities. Yet they have not succeeded in soliciting the civil society organizations' participation, and no visible improvements can be associated with their environmental performance. Although constituents have highly significant level of understanding of the Valdez Principles and the Philippine Agenda 21, these key components of managing green have yet to be institutionalized and centered in the environmental program of the barangays. To bring managing green closer to the grassroots, a training-seminar intervention is recommended with accompanying design to serve as practical guide for implementation."